PENGETAHUAN MAHASISWI FIKES UIN JAKARTA TENTANG DAMPAK KOSMETIK BERBAHAN MERKURI BAGI KESEHATAN KULIT - Firyal Idzka Azzahra; Zahratun Nihaya; Raihani Muamalia (Program Studi Kesehatan Masyarakat Universitas Sari Mutiara Indonesia, 2021)
Facial skin care technology develops along with the development of science and technology. Having clean and bright skin quickly becomes everyone's dream. However, it makes consumers not pay attention to the ingredients contained in the cosmetics used. One of the dangerous chemicals contained in cosmetics, namely mercury. Cosmetics containing mercury can pose a risk to skin health. The impact of mercury on skin health starts from rashes to swollen faces. This study uses a descriptive survey method by collecting data through a questionnaire. The population of this study were students of the Faculty of Health Sciences, UIN Jakarta, who were active. The sample used random sampling as many as 41 people. The results of this study are 34 female students know about the impact of using mercury cosmetics, 8 female students have used mercury cosmetics. Researchers hope this research can provide knowledge for the public, especially female students to be more careful in choosing cosmetics so as to minimize the risk of skin health.